PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL INTERAKTIF DENGAN INTEGRASI AUGMENTED REALITY (AR) FASE F PADA MATA PELAJARAN TEKNOLOGI PERKANTORAN SMKN 12 JAKARTA - Wiwit Aulia; Darma Rika Swaramarinda; Ferry Setyadi Atmadja (STKIP Subang, 2026)
The lack of learning media that serve as both the primary learning resource and provide visual reinforcement in the Office Technology subject at SMKN 12 Jakarta motivated this study. This study aimed to develop an interactive digital flipbook integrated with Augmented Reality (AR) that is feasible and effective for learning. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The results showed that the developed learning media were highly feasible and effective, with an average feasibility score of 90.79% and an N-Gain score of 0.77. Therefore, the interactive digital flipbook integrated with AR is considered highly feasible and effective as the primary learning resource for the Office Technology subject (Phase F) at SMKN 12 Jakarta.